Adoption of Fintech by Labuhanbatu Students - Ade Parlaungan Nasution; Yudi Prayoga; Muhammad Yasir Arafat Pohan; Zulkifli Musannif Efendi Siregar (Universitas Pendidikan Ganesha, 2023)
The financial services industry is witnessing massive structural changes due to various technological innovations. The ubiquitous innovation known as Financial Technology (Fintech) is changing traditional banking and corporate finance. The use of Fintech has now become widespread and has changed people's financial patterns. Fintech provides various conveniences in various activities related to payments, money transfers, and even the management of savings itself, even the use of Fintech currently plays a significant role in the progress of small and medium enterprises. In various big cities in Indonesia, small community-owned businesses are familiar with using Fintech as payment. However, based on the observations of researchers, it is known that in Labuhanbatu, the use of Fintech is still infrequent. Therefore, this study aims to analyses the factors which affect the intention to use Fintech in Labuhanbatu. This study uses a quantitative approach and data analysis using the Smart PLS3 software. The sample in this study was students in Labuhanbatu. This study uses the PLS technique which is a variance-based SEM which is suitable for this study due to the sample size and complexity of the hypothesis. From the study's results, it was found that all predictive variables had a positive and significant influence on the intention to use Fintech by Labuhanbatu students.